Implementasi Arsitektur Keamanan Terintegrasi IDS, WAF Dan FIM Berbasis Wazuh Pada Platform Open Jurnal System Mengacu Pada NIST Cybersecurity Framework - William Carey Kornelius; Pitrasacha Adytia; Ahmad Fahrijal Pukeng (JURIKOM (Jurnal Riset Komputer), 2026)
The utilization of Open Journal Systems (OJS) as a scientific publishing platform faces significant security threats, including SQL Injection, Cross-Site Scripting (XSS), and webshell injection, which may compromise data integrity and service availability. This study aims to design and evaluate an integrated security architecture based on Wazuh through the implementation of an Intrusion Detection System (IDS), Web Application Firewall (WAF), and File Integrity Monitoring (FIM) using the NIST Cybersecurity Framework approach. The research methodology includes vulnerability identification across 11 journals in 7 universities, the development of a defense-in-depth architecture, and controlled penetration testing based on OWASP Top 10 scenarios. Testing results from 30 attack scenarios demonstrate a 100% detection rate for SQL Injection and webshell injection, and an 80% detection rate for XSS attacks. The system successfully blocks malicious requests with 403 Forbidden responses and generates real-time alerts through centralized log correlation in Wazuh. However, potential false positives were observed in several generic security rules, indicating the need for rule fine-tuning to align with OJS traffic characteristics. Overall, the integrated security approach measurably enhances threat detection and incident response capabilities.